A qualitative analysis of school psychology trainers' perspectives on evidence-based practices. Issue 2 (3rd April 2021) - Gonzalez, Jorge E.; Stoiber, Karen C.; Clayton, Rebecca J.; Keller-Margulis, Milena; Reddy, Linda A.; Forman, Susan G.
ABSTRACT: This study examined school psychology faculty beliefs, attitudes, and perceptions regarding the status of graduate training in evidence-based assessment and intervention. The perspectives of a national sample of faculty in the U.S. were obtained through an online survey. A qualitative examination of faculty responses provided an understanding of the current state of instruction and dissemination of evidence-based assessment (EBA) and evidence-based intervention (EBI) in school psychology training programs. Four themes emerged from a content analysis of evidence reflecting faculty perspectives about EBAs and EBIs including barriers, facilitators, courses in EBI/EBAs, and supports for EBI/EBA implementation. Faculty provided 991 barrier-oriented comments compared to 276 support-oriented comments. The findings of this study provide insight into faculty notions about the status of evidence-based intervention and assessment in the training of school psychologists, as well as ways to overcome barriers and support a shift toward implementation science in the field.